Analysis of popular types of gto standards among middle-aged people - Fedorova, N.I.; Dardanova, N.A.; Vinogradova, L.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to analyze the most popular types of GTO tests among middle-aged people and develop recommendations for optimizing the process of preparing and passing standards. Methods and structure of the study. The analysis of scientific and methodological literature, the analysis of data on the fulfillment of the state requirements of the GTO for 2023 in the subjects of the Russian Federation based on the statistical reports of the GTO for 2023, as well as methods of mathematical statistics. The article is based on the results of the implementation of the state task ‘Improving the GTO based on the results of an expert-analytical analysis of the implementation of the GTO in the Russian Federation.’ Results and conclusions. In 2023, the total number of middle-aged people participating in GTO tests decreased by 9.3%. At the same time, there was an increase in female participants by 18.4% and a decrease in male participants by 6.6%, respectively. An analysis of the popularity of test types among people aged 45 to 59 (XIII-XV levels) participating in the implementation of state GTO requirements in 2023 gave an idea of which types of tests are most in demand and accessible for this age group, as well as identified problem areas and developed recommendations for optimising the process of preparation and passing the standards. The implementation of these recommendations will increase the accessibility and attractiveness of the GTO complex, increase the number of participants and ultimately strengthen the health of the nation.